2010
DOI: 10.1007/s10459-010-9259-y
|View full text |Cite
|
Sign up to set email alerts
|

Medical educators’ social acts of explaining passing underperformance in students: a qualitative study

Abstract: Passing underperformance in students is ubiquitous across health and social care educators and is intimately related to the subsequent welfare of patients: underperforming students may become underperforming practitioners. This paper aims to examine how medical educators construct passing underperformance through an analysis of their social act of explaining such behaviours in peer-group settings. Ten focus groups were conducted with 70 medical educators across two UK schools with different curricular/assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Compared with naturalistic talk around socially acceptable behaviours, 7 our students employed substantially more non‐Reason explanations (CHRs and EFs), desire and unmarked Reasons when explaining their compliance in order to portray themselves in a more positive light, as has been found in previous research in which students and medical educators have described their negative actions 9,17 . What is striking about our findings is the high proportion of EF explanations for compliance and refusal behaviours.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Compared with naturalistic talk around socially acceptable behaviours, 7 our students employed substantially more non‐Reason explanations (CHRs and EFs), desire and unmarked Reasons when explaining their compliance in order to portray themselves in a more positive light, as has been found in previous research in which students and medical educators have described their negative actions 9,17 . What is striking about our findings is the high proportion of EF explanations for compliance and refusal behaviours.…”
Section: Discussionsupporting
confidence: 53%
“…Compared with naturalistic talk around socially acceptable behaviours, 7 our students employed substantially more non-Reason explanations (CHRs and EFs), desire and unmarked Reasons when explaining their compliance in order to portray themselves in a more positive light, as has been found in previous research in which students and medical educators have described their negative actions. 9,17 What is striking about our findings is the high proportion of EF explanations for compliance and refusal behaviours. Other research has found that EFs occur seven to eight times more frequently in explanations of difficult rather than easy behaviours 7 and this is likely to account for our findings: both compliance and refusal behaviours are difficult, as illustrated in the emotional talk employed by students when narrating their intimate examination dilemmas.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Distancing indicates the influence of social desirability (25), that is, the drive for approval from others, which was also apparent at interview in the attitude of some clinicians who were self-deprecatory, apologetic and not wishing to appear critical of senior staff. According to Monrouxe et al '… when we explain our behaviour to others we are motivated to provide a convincing story portraying us in a positive light' (9). Social desirability could account for the paradoxical remarks of one respondent who said she rarely marked down clinical performance, but later said she would not hesitate to fail a student who performed poorly because of her duty of care to the patient.…”
Section: Discussionmentioning
confidence: 99%